2018
DOI: 10.3390/ijms19092529
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Significance of VHL Gene Alteration in Clear-Cell Renal Cell Carcinoma: An Updated Meta-Analysis and Review

Abstract: The von Hippel-Lindau (VHL) gene is inactivated frequently in sporadic clear-cell renal cell carcinomas (ccRCCs) by genetic alteration (mutation, loss of heterozygosity, or promoter hypermethylation). However, the pathological or prognostic significance of VHL gene alteration has not been well defined. We conducted this meta-analysis to evaluate the association between VHL alteration and clinopathologic findings in ccRCCs. We performed a systematic computerized search of online databases, including PubMed, EMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 42 publications
(125 reference statements)
2
25
0
1
Order By: Relevance
“…The integration of radiomics and genomics data could be valuable and enable more precise survival prediction. However, the prognostic role of radiomics and other omics features is still controversial, for example, few studies demonstrated that VHL mutation could predict patient survival [ 9 ], and many genes and pathways still lack related evidence. Moreover, the correlation between radiomics and other omics features is complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of radiomics and genomics data could be valuable and enable more precise survival prediction. However, the prognostic role of radiomics and other omics features is still controversial, for example, few studies demonstrated that VHL mutation could predict patient survival [ 9 ], and many genes and pathways still lack related evidence. Moreover, the correlation between radiomics and other omics features is complex.…”
Section: Discussionmentioning
confidence: 99%
“…Several targeted blockers of vascular endothelial growth factor pathway (e.g., sorafenib, axitinib) have been approved for treatment of metastatic RCC [ 8 ]. However, the capability of VHL mutation as a prognostic factor was not significant in ccRCC [ 9 ]. Conversely, PBRM1 mutation was associated with shorter survival, early tumor progression, and response to immune checkpoint therapies in ccRCC patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Изучение связи мутаций VHL с этиологией, прогрессированием и прогнозом скПКР привело к накоплению большого количества противоречивых данных. Метаанализ результатов 10 публикаций, включивших 1082 пациента со скПКР, показал, что изменения гена VHL незначительно ассоциированы с клиническими характеристиками заболевания и общей выживаемостью пациентов [22]. Тем не менее изучение мутаций VHL важно, так как для прогрессирования скПКР и, возможно, для прогноза заболевания определенное значение имеет сочетание мутаций VHL и других генов [23][24][25].…”
Section: экспериментальные статьиunclassified
“…In addition, CCRCC has the worst prognosis among the common epithelial kidney tumors ( 5 ). Recently, significant progress has been made in the current understanding of CCRCC development; for example, the von Hippel-Lindau tumor suppressor gene is inactivated frequently by genetic alteration ( 6 ). However, the molecular mechanisms underlying CCRCC pathogenesis remain unknown.…”
Section: Introductionmentioning
confidence: 99%